2008
DOI: 10.1073/pnas.0712307105
|View full text |Cite
|
Sign up to set email alerts
|

Auxin acts as a local morphogenetic trigger to specify lateral root founder cells

Abstract: Plants exhibit an exceptional adaptability to different environmental conditions. To a large extent, this adaptability depends on their ability to initiate and form new organs throughout their entire postembryonic life. Plant shoot and root systems unceasingly branch and form axillary shoots or lateral roots, respectively. The first event in the formation of a new organ is specification of founder cells. Several plant hormones, prominent among them auxin, have been implicated in the acquisition of founder cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
489
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 561 publications
(507 citation statements)
references
References 31 publications
8
489
1
9
Order By: Relevance
“…Recent results reveal its independence from the basic auxin signaling pathway. A mechanism where the asymmetric distribution of auxin itself acts as a morphogenic trigger to prime pericycle cells was proposed (Dubrovsky et al, 2008). Together, these data point out the crucial role of auxin gradients in root development.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Recent results reveal its independence from the basic auxin signaling pathway. A mechanism where the asymmetric distribution of auxin itself acts as a morphogenic trigger to prime pericycle cells was proposed (Dubrovsky et al, 2008). Together, these data point out the crucial role of auxin gradients in root development.…”
mentioning
confidence: 63%
“…For instance, the acquisition of founder cell identity, cell cycle reactivation, and LR emergence all correlate with and require local auxin accumulation in specific cell types (Dubrovsky et al, 2008;Fukaki and Tasaka, 2009). Recent studies have suggested that the coordination of polar auxin transport by auxin influx carriers (AUX/LAX) and auxin efflux carriers (PIN) is responsible for establishing an auxin gradient along the root with specific local maxima that regulate LR development (Bainbridge et al, 2008;Ditengou et al, 2008;Laskowski et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
The phytohormone auxin acts as a prominent signal, providing, by its local accumulation or depletion in selected cells, a spatial and temporal reference for changes in the developmental program [1][2][3][4][5][6][7] . The distribution of auxin depends on both auxin metabolism (biosynthesis, conjugation and degradation) [8][9][10] and cellular auxin transport [11][12][13][14][15] .
…”
mentioning
confidence: 99%
“…For example, when Arabidopsis root pericycle cells undergo reprogramming into lateral root, lateral root growth is initiated. At this time, auxin gathers in the pericycle cells adjacent to xylem vessels [29]. Furthermore, auxin has other effects on lateral roots, including the development of root systems, the structure of lateral root primordia, and root branching from parent roots [30].…”
Section: Auxin-regulated Root Tips Life-cyclementioning
confidence: 99%